Autopercepção da mastigação e fatores associados em adultos brasileiros - Ana Paula Gasparini Braga (2011)
INTRODUCTION: The mastication is one of the most important functions on the stomatognathic system, and it is related to nutrition, growth and craniofacial development, the orofacial musculature maturation; to the occlusal stability to the temporomandibular joint stability. There are only few practical studies about the topic in adults. OBJECTIVES: The aim of the study was to estimate the prevalence of the mastication self perception as good, regular and bad in Brazilian adults; and investigate the facts related to the regular and bad self-perception. METHODOLOGY: Transversal study among 13.431 adults (35 to 44 years old), living in urban and rural areas of 250 Brazilian municipal districts, participants of the SB Brazil Project. Professional dentists collected all the data at the municipal districts, through structured interviews and dental examinations. The external environment, individual characteristics, behaviors related to the oral health, normative and subjective conditions were considered in identifying the associated items to the mastication self perception (regular and bad). The descriptive analysis was done through bivaried 2 (p<0,20), multivaried with multinominal logistical regression (p<0,05),with 95% CI. RESULTS: 55.6% had the mastication classified as good, 24,9% as regular and 19,5% as bad. In the bivaried analysis, all the factors were associated to the regular or bad mastication self perception (p<0,20). The chances to realize as bad were smaller in men and in those who used partial prosthesis or total; self declared brown, didnt receive information on how to avoid dental/oral problems, presented 13-22, 3-12, 0-2 remaining teeth, require partial prosthesis or total, noted the oral health as regular or bad/very bad reported tooth and gun pain and need for dental treatment. The chances of realizing how regular were smaller among men among those with lower educational levels of 4 to 7 years and 0 to 3 years; higher among the people living in the north region, didnt receive information on how to avoid oral problems, presented 13-22, 3-12, 0-2 remaining teeth required partial prosthesis or total, noticed the oral health as regular or bad / vary bad reported tooth and gun pain and the need for dental treatment.CONCLUSIONS: The prevalence of people that have the mastication as regular or bad is high in the Brazilian adult population. The external factors as well as the factors related to the oral health habits, and the normative and subjectives conditions were associated to the worse mastication. It is highlighted among the investigated factors, the magnitude of the subjective conditions associated, reinforcing the importance of these indicator on oral health.